Analysis of geothermal fluid chemical characteristics and genetic model—A case study from the urban area of Jingmen China - Liu, Rui; Li, Hongmei; Zhao, Zhan; Zhang, Zeyu (Frontiers in Earth Science, 2023)
Over the years, scholars both at home and abroad have been committed to the research of geothermal fluid chemistry and genetic model, and geochemical and isotopic methods are usually the first choice for evaluation. In this paper, the characteristics of geo-thermal fluids and their genesis patterns in the Jingmen urban area are analyzed and studied by comprehensive utilization of techniques such as hydrochemistry, trace elements, and isotope analysis. The results show that the water chemical type of surface water and groundwater is Ca-HCO4 type, while the geothermal fluid belongs to the Ca-SO4 type. The recharge source of the geo-thermal fluid is the infiltration recharge of meteoric precipitation, and the recharge altitude is 395-435m, and the geothermal fluid is modern water (less than 5-10 years old). The water-rock reaction has not reached equilibrium, and the dissolution is still in progress. The estimated mixing ratio of cold-water ranges from 30-40%. The thermal reservoirs are mainly calcareous dolomite and dolomite of the Lower Triassic Jialingjiang Formation (T1j). The red sandstone and mudstone of the Upper Cretaceous Paomagang Formation (K2p) distributed in the area are good caprocks of the geothermal field. The geothermal energy in the urban area of Jingmen is a system of lateral "seepage". Thermal water surges up along the Jingmen fracture and fracture zone, forming a relatively high-temperature center, and a part of its “seeps” laterally into the shallow pore aquifer or pore-fracture aquifer, which mixed with the cold water in it to form medium and low-temperature hot water around the center of the geothermal area.